SIRT1 and thrombosis - Bettiol, Alessandra; Urban, Maria Letizia; Emmi, Giacomo; Galora, Silvia; Argento, Flavia Rita; Fini, Eleonora; Borghi, Serena; Bagni, Giacomo; Mattioli, Irene; Prisco, Domenico; Fiorillo, Claudia; Becatti, Matteo (Frontiers in Molecular Biosciences, 2024)
Thrombosis is associated with a relevant burden of morbidity and mortality worldwide, with a complex and multifactorial pathogenesis. Recent studies have shown that SIRT1, belonging to the sirtuin family of NAD+-dependent deacetylases, plays a crucial role in regulating thrombosis, modulating key pathways including endothelial activation, platelet aggregation, and coagulation. Furthermore, SIRT1 displays anti-inflammatory activity both in vitro, in vivo and in clinical studies, particularly via the reduction of oxidative stress. On these bases, several studies have assessed the therapeutic potential of targeting SIRT1 for the prevention of thrombosis. This review provides a comprehensive and critical overview of the main preclinical and clinical studies and of the current knowledge of the role of SIRT1 in thrombosis.